School Leaders’ Attitudes, Expectations, and Beliefs Starting a Character Education Training in Latvia - Fernández González, Manuel Joaquín; Surikova, Svetlana (Acta Paedagogica Vilnensia, 2022)
This article explores school leaders’ expectations and beliefs when starting a professional development course about character education in Latvia. The survey used mixed methods, involved 30 participants, and was conducted in 2020. School leaders expected to enhance their practical know-how in this field, the desired opportunities for personal reflection and sharing with colleagues, and believed that shared values and a friendly atmosphere were the key points. The findings can be useful for future similar initiatives.